Thiazolidinedione Response in Familial Lipodystrophy Patients with LMNA Mutations: A Case Series - Luedtke, A.; Boschmann, M.; Colpe, C.; Engeli, S.; Adams, F.; Birkenfeld, A. L.; Haufe, S.; Rahn, G.; Luft, F. C.; Schmidt, H. H.-J.; Jordan, J. (Hormone and Metabolic Research, 2012)
Type 2 familial partial lipodystrophy (FPLD2) patients show impaired glucose and lipid metabolism resulting from lipodystrophic ‘lipid pressure’ and an intrinsic defect in skeletal muscle metabolism. Since mutated lamin A may interfere with peroxisome proliferator activator gamma (PPARγ) expression, we hypothesized that PPARγ stimulation improves fat distribution and metabolic abnormalities in these patients. 5 nondiabetic FPLD2 patients were treated with rosiglitazone over 12 months. We assessed body composition, body fat distribution, and skinfold thickness/subcutaneous tissue thickness. We also determined venous glucose, insulin, and free fatty acid (FFA) concentrations, and respiratory quotient (RQ) before and during oral glucose tolerance testing. Adipose tissue and muscle fasting and postprandial metabolism were studied by microdialysis. Within 12 months treatment, hip circumference increased from 93.6±2.78 cm to 96.2±2.3 cm (p<0.05). Rosiglitazone reduced fasting glucose levels and liver transaminases. Baseline and postprandial FFA concentrations were significantly lower after 12 months treatment. RQ and muscle interstitial pyruvate and lactate did not respond to treatment. We conclude that PPARγ stimulation with rosiglitazone modestly improves glucose metabolism in FPLD2 patients presumably through proximal adipose tissue expansion. The intrinsic muscular metabolic defect does not respond to rosiglitazone.
Keywords: laminopathies; adipose tissue; muscle; microdialysis; calorimetry